Lipidomic analyses reveal the dysregulation of oxidized fatty acids (OxFAs) and acyl-carnitines (CARs) in major depressive disorder: a case-control study - Lei He; Na Duan; Chong Wang; Ru Shan; Jing Li; Lin Wang; Qiuli Liu; Junwei Tao; Li Liu; Xiaoliang Ma; Bing Cao (BMC Psychiatry)
Abstract Background Growing data indicated that individuals diagnosed with major depressive disorder (MDD) had widespread inflammation, oxidative stress, and metabolic dysregulation. The objective of our study was to detect alterations in lipids of individuals with MDD, with the ultimate aim of developing potential biomarkers that may contribute to the diagnosis and treatment of MDD. Methods The current study was a single-center cross-sectional case-control design. Serum samples were obtained from 107 individuals diagnosed with MDD and 97 healthy controls (HC) aged 18 to 60 years. Lipidomics analysis was performed using an Ultimate 3000 UHPLC system coupled with a Q-Exactive HF MS platform. All data were processed using the specialized online software Metaboanalyst 5.0. Results Based on the filtering criteria of false discovery rate (FDR) -adjusted P < 0.05, variable importance in projection (VIP) > 1.5, and fold change (FC) > 2.0 or < 0.5, a total of 40 lipids were identified as significantly different. In patients with MDD, we observed an increase in 11 types of oxidized fatty acids (OxFAs) and a decrease in 5 types of OxFAs. Additionally, we found that 8 types of acyl-carnitines (CARs) decreased, primarily comprising singular carbon chain structures, while 3 types of CARs increased, all with numerical carbon chain patterns. Lipid profiles yield a high area under the receiver operating characteristic (ROC) curve for differentiating MDD, with the most prominent ROC ranking being mostly attributed to OxFAs. Conclusions Our research found significant variations in lipid levels, specifically increased OxFAs and decreased CARs, in individuals with MDD compared to HCs. Supplementation with PUFAs and acyl-carnitines warrants further investigation as a potential strategy for the management of MDD. Nevertheless, further investigation is necessary, and exercise prudence is required when examining and implementing their forms and proportions.